2011
DOI: 10.1111/j.1741-3737.2011.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Associations Between Connectedness and Autonomy Among Korean Adolescents: Compatible or Antithetical?

Abstract: The primary goal of this study was to examine the longitudinal reciprocal relationships between connectedness to parents and autonomy among Korean adolescents using five annual waves of the Korea Youth Panel Survey. The sample consisted of 3,449 adolescents, whose mean age was 13.79 years at Wave 1. Contrary to the mainstream findings in individualistic societies that autonomy is not necessarily inimical to connectedness to parents, the present study convincingly suggested that Korean adolescents' pursuit of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
1
9
0
2
Order By: Relevance
“…Our results also indicated that the emotional autonomy of young college students correlates negatively with perceived family social support, with those with greater emotional autonomy having less confidence in the support they feel they receive from their parents. These results are consistent with the findings of previous studies by Neff and Harter () and Yu (), who found an association between high levels of emotional autonomy and weaker, less cohesive family structures.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results also indicated that the emotional autonomy of young college students correlates negatively with perceived family social support, with those with greater emotional autonomy having less confidence in the support they feel they receive from their parents. These results are consistent with the findings of previous studies by Neff and Harter () and Yu (), who found an association between high levels of emotional autonomy and weaker, less cohesive family structures.…”
Section: Discussionsupporting
confidence: 93%
“…However, other authors dispute the argument that achieving emotional autonomy is a developmental task, supporting instead the theory that adolescents who feel more emotionally autonomous from their parents perceive lower quality, less affection and less love in their relationships with them (Ryan & Lynch, ; Zimmer‐Gembeck, Madsen & Hanisch, ). These studies have also shown that high levels of emotional autonomy are associated with challenges in family relationships during adolescence and emerging adulthood, less cohesive family structures marked by a lack of emotional intimacy and communication, and more difficult parent‐child relationships (Neff & Harter, ; Yu, ). Thus, according to this latter perspective, high emotional autonomy is associated, at least during these years, with feelings of insecurity, negative self‐concept, depression and other behaviors linked to internalizing problems (Delhaye, Kempenaers, Linkowski, Stroobants & Goossens, ; Ryan & Lynch, ).…”
Section: Introductionmentioning
confidence: 99%
“…That is, boys and girls reported similar levels of dispositional optimism, and the same pattern applied to the father's ratings. As discussed earlier, dispositional optimism is relatively responsive to environmental factors (Atienza et al, 2004;Robinson-Whelen et al, 1997); thus, similar levels of dispositional optimism for both boys and girls could be partly interpreted to mean that boys and girls are treated quite similarly in South Korea (Yu, 2011).…”
Section: Downloaded By [Uq Library] At 16:34 04 November 2014mentioning
confidence: 96%
“…We also know little about whether SES is significantly linked to paternal emotional expressiveness within the family. However, the higher the SES status of the parents, the more supportive and nurturing are their child-rearing practices (e.g., Yu, 2011); thus, it is expected that the higher SES status of the fathers, the more positive and less negative expressive they are.…”
Section: Socioeconomic Differencesmentioning
confidence: 98%
“…Thus, self‐esteem changes over the course of adolescence. However, the overwhelming number of studies on trajectories of self‐esteem in adolescence have been limited to Western countries; therefore, much remains to be learned concerning longitudinal changes in adolescent self‐esteem in non‐Western countries, where the social or interpersonal self is more strongly held (Muramoto, Yamaguchi, & Kim, ; Yik, Bond, & Paulhus, ; Yu, ).…”
Section: Introductionmentioning
confidence: 99%